Cu-Zr nanoglasses: Atomic structure, thermal stability and indentation properties. (1st September 2017) - Nandam, Sree Harsha; Ivanisenko, Yulia; Schwaiger, Ruth; Śniadecki, Zbigniew; Mu, Xiaoke; Wang, Di; Chellali, Reda; Boll, Torben; Kilmametov, Askar; Bergfeldt, Thomas; Gleiter, Herbert; Hahn, Horst
Abstract: The structure of Cu50 Zr50 metallic nanoglasses, their thermal stability and mechanical performance are studied in the present paper. Elemental segregation of Cu and Zr is observed in consolidated nanoglasses. A segregation model is proposed with Cu rich interfaces and Zr rich relaxed cores which explains the observed thermal and mechanical properties of nanoglasses. The interfacial regions with high free volume and enriched with Cu act as nucleating sites for the crystallization reaction, increasing the crystallization temperatures in nanoglasses compared to the melt-spun ribbon of the same composition. The hardness and Young's modulus increase as well for the nanoglasses compared to melt-spun ribbons. Metallic nanoglasses deform homogenously, while melt-spun ribbons reveal the formation of shear bands during indentation. It is proposed that the interfacial regions, which are sources of high free volume act as nucleating sites for the formation of numerous shear transformation zones giving rise to homogeneous deformation in nanoglasses. Graphical abstract: